Rehabilitation and renovation of cocoa (Theobroma cacao L.) agroforestry systems. A review - Somarriba, E.; Peguero, F.; Cerda, R.; Orozco Aguilar, L.A.; López Sampson, A.; Leandro-Muñoz, M.E.; Jagoret, P.; Sinclair, Fergus L. (Springer, 2021)
In this review, we (1) explore the diversity of contexts, driving forces, stakeholders and recommended management practices involved in Rh/Re initiatives in key cocoa-producing countries; (2) summarise the often conflicting views of farmers and extension agents on Rh/Re programmes; (3) review the evidence of age-related changes in planting density and yield of cocoa, given the weight of these variables in Rh/Re decision processes; (4) describe the best known Rh/Re systems and their most common management practices; (5) propose an agroforestry Re approach that overcomes the limitation of current Rh/Re diagnosis protocols, which do not consider the regular flow of food crop and tree products, and the need to restore site soil quality to sustain another cycle of cultivation of cocoa at the same site; and (6) explore the effects of climate change considerations on Rh/Re decision-making and implementation processes.